Optimasi Algoritma K-Nearest Neighbor dengan Particle Swarm Optimization untuk Klasifikasi Penyakit Liver - Bagus Prindo Sugihartono Putro; Handayani, Yuni; Hidayat, Taufik (Fakultas Komputer Dan Desain, 2024)
This study optimizes the K-Nearest Neighbor (KNN) algorithm using Particle Swarm Optimization (PSO) for liver disease classification. With the increasing number of liver disease patients due to unhealthy lifestyles, early detection is vital. The disease is often asymptomatic early on, earning it the name